Preschool Inquiry-Based Mathematics in Practice: Perspectives of Teachers and Parents - Karademir, Abdulhamit; Akman, Berrin (My University, 2021)
An Inquiry-Based Mathematics Activities Module (IBMAM) consisting of integrated and child-centered activities was developed. IBMAM provides preschoolers 60-72 months of age with the opportunity to develop mathematical and inquiry skills and use them actively to construct their own learning. The present study aims to investigate the effects of IBMAM on preschoolers. Teachers’ and parents’ views were obtained, and long-term observations (16 weeks) were performed. Phenomenology, which is a qualitative research design, was used in this study. The study sample consisted of a pre-school teacher of a kindergarten (Sincan, Ankara) and her children’s parents in the academic year of 2016-2017. Semi-structured interviews were conducted with the teacher to assess the postIBMAM process, changes in their views of math and math education, the effects of IBMAM on preschoolers’ math skills and changes in the classroom. Preschoolers’ parents’ were also interviewed to evaluate changes in preschoolers at home. To support the results of the interviews, unattended and structured classroom observation was conducted twice a week for four months on certain dates. Instant field notes were taken during each observation, which was also videotaped. Data were analyzed using inductive content analysis. Results showed that IBMAM contributed to all areas of development by providing a fun and educational setting that increased preschoolers’ motivation. In the observations, it was understood that the applied module gave pre-school children different perspectives, encouraged active participation, enabled learning to continue, and help enabled pre-school children to use their scientific process skills more frequently. Moreover, parents noticed positive changes in their children, and therefore, were optimistic about the future.